Berlian: Belajar dengan Kreativitas Anak dalam Media Pembelajaran untuk Meningkatkan Pembelajaran Matematika - Witri Lestari; Hawa Liberna; Lin Mas Eva (Indo Publishing, 2025)
This community service program was conducted in collaboration with the Kampung Sahabat Foundation, a social community focused on empowering and educating marginalized children, particularly children from scavenger families living around the At-Tin Mosque, Ceger, Cipayung, East Jakarta. The theme of the program was